Cardiovascular Complications in Pheochromocytoma and Paraganglioma: Does Phenotype Matter? - Petrák, Ondřej; Krátká, Zuzana; Holaj, Robert; Zítek, Matěj; Nguyen Nikrýnová, Thi; Klímová, Judita; Kološová, Barbora; Waldauf, Petr; Michalský, David; Novák, Květoslav; Markvartová, Alice; Zlatohlávek, Lukáš; et al. (Hypertension (Dallas, Tex. 1979), 2024)
BACKGROUND: Adrenaline-producing tumors are mostly characterized by a sudden release of catecholamines with episodic symptoms. Noradrenergic ones are usually less symptomatic and characterized by a continuous overproduction of catecholamines that are released into the bloodstream. Their effects on the cardiovascular system can thus be different. The aim of this study was to determine the prevalence of cardiovascular complications by catecholamine phenotype. METHODS: We retrospectively analyzed data on the prevalence of cardiovascular events in 341 consecutive patients with pheochromocytoma and paraganglioma treated from 1995 to 2023. Biochemical catecholamine phenotype was determined based on plasma or urinary catecholamines and metanephrines. RESULTS: According to the phenotype, 153 patients had noradrenergic pheochromocytoma and paraganglioma and 188 had adrenergic pheochromocytoma and paraganglioma. In the whole sample, the incidence of serious cardiovascular complications was 28% (95 patients), with no difference between the phenotypes or sexes. The noradrenergic phenotype had significantly more atherosclerotic complications (composite end point of type 1 myocardial infarction and symptomatic peripheral artery disease; odds ratio, 3.58 [95% CI, 1.59-8.83]; P=0.003), while the adrenergic phenotype more often had type 2 myocardial infarction and takotsubo-like cardiomyopathy (OR, 0.24 [95% CI, 0.09-0.57]; P=0.002). These changes remained even after adjustment for conventional risk factors of atherosclerosis. CONCLUSIONS: We found a 28% incidence of cardiovascular complications in a consecutive group of patients with pheochromocytoma and paraganglioma. Patients presenting with a noradrenergic phenotype have a higher incidence of atherosclerotic complications, while the adrenergic phenotype is associated with a higher incidence of acute myocardial damage due to takotsubo-like cardiomyopathy.